Essential statistics, regression, and econometrics - Smith, Gary, 1945- (Academic Press, 2012)
Essential Statistics, Regression, and Econometrics provides students with a readable, deep understanding of the key statistical topics they need to understand in an econometrics course. It is innovative in its focus, including real data, pitfalls in data analysis, and modeling issues (including functional forms, causality, and instrumental variables). This book is unusually readable and non-intimidating, with extensive word problems that emphasize intuition and understanding. Exercises range from easy to challenging and the examples are substantial and real, to help the students remember the technique better. Readable exposition and exceptional exercises/examples that students can relate toFocuses on key methods for econometrics students without including unnecessary topicsCovers data analysis not covered in other textsIdeal presentation of material (topic order) for econometrics course.